Sistem Administrasi dan Layanan Pelanggan Berbasis Web dan Android Mobile untuk Kursus Bahasa Mandarin X - Nyoto William Wijaya; Henry Novianus Palit; Lily Puspa Dewi (Jurnal Infra, 2016)
Chinese Language Course Institute X, founded in 2010, is located in Surabaya. Presently, Chinese Language Course Institute X has not used any information system, so everything is recorded manually, from the administrative matter, course schedule, new student registration, attendance checklist, until the financial matter. A lot of archives must be stored and it takes so much time to find particular data. Therefore, an administrative and service information system for Chinese Language Course Institute X will be developed using the Web and mobile application technologies.The Web-based application will help the Institute’s administrator in managing course schedule, calculating salaries, marking students’ and teachers’ attendance, storing and retrieving financial data. The Android-based application, on the other hand, is aimed to help teachers and students in view course schedule, making changing request schedule, view attendance, input and view test scores, view salary report, upload and download teaching materials.Experimental results show that the mobile application can run smoothly in mobile devices with Android 4.2 (Jelly Bean) and Android 4.4 (Kitkat) operating systems. All the developed features mentioned above work well and can help users obtaining the course-related information.